Modeling of lead (II) adsorption on sodium hydroxide treated rice husk: fixed-bed studies - Garba, Abdurrahman; Basri, Hatijah; Nasri, Noor Shawal; Siddiq, Umar Hayatu; Abdul Rahman, Abdul Rasheed (UTM Press., 2017)
Sodium hydroxide treated rice husk was explored as an adsorbent for the removal of lead (II) ions from aqueous solutions in a column studies. This paper evaluate the effect of flow rates of 3 mL/min and 9 mL/min; bed depth of 0.9 cm, 1.8 cm and 2.8 cm and influent lead concentration of 5 mg/L and 20 mg/L on the adsorption capacity of the sample in fixed-bed mode were investigated. The highest adsorption capacity of 78 % using 20 mg/L initial lead (II) ions solution was achieved at flow rate of 9 mL/min and bed depth of 2.8 cm. The experimental results obtained from the adsorption studies were correlated with the Thomas, Adams– Bohart and Yoon–Nelson models. The results of the adsorption parameters showed that, Adams–Bohart model fitted the adsorption studies well over all the other models.